PELATIHAN PEMBUATAN PRODUK KECANTIKAN BERBAHAN DASAR GARAM LAUT DI DESA LAMPANAH, ACEH BESAR - Nabila Ukhty; Yasrizal Yasrizal; Anhar Rozi (Jurnal Marine Kreatif, 2020)
Salt is a chemical compound that is generally derived from sea water, with the chemical name Sodium Chloride (NaCl). Salt can be obtained in three ways, namely through evaporation of seawater by sunlight, rock mining (rock salt mining) and from brine wells (brine). Lampanah Village is one of the Villages located on the coast of Kabuoaten Aceh Besar, with the majority of its residents living as salt farmers. The implementation of the training program for making beauty products made from sea salt was carried out in Lampanah Village, Aceh Besar District. The training method used in the utilization of sea salt consists of 2 stages, namely extracting information about salt and training and direct practice of processing sea-based products into spa salt, salt masks and salt face scrubs. improve the skills of salt farmers in Lampanah Village, Aceh Besar in processing salt into high-value-selling products. These products include salt masks, salt scrubs and spa salts. In addition, it is hoped that these products will become local products typical of Lampanah Village, Aceh Besar.